The roles of community in the administration of secondary schools in Ekiti State, Nigeria - Olowo, Busuyi Francis; Adebola, Solomon Temitope; Fashiku, Christopher Oluwatoyin; Alabi, Festus O (Penerbit Universiti Kebangsaan Malaysia, 2019)
Community roles in secondary schools are very fundamental for the development of education. Mutual co-operation between schools and the community is very significant for the ultimate goals of education to be realized. This paper reports a survey done to determine the roles of community in the administration of secondary schools in Ekiti State, Nigeria with regards to provision of material, financial support, staff welfare and their relationship with the schools. 27 principals and 409 teachers were randomly selected as samples. Role of Community in the Administration Secondary School Questionnaire (RCASSQ) was used to collect the data. The data was analysed descriptively. The result showed that the community play their roles in providing materials (= 2.32), rendering financial support (= 2.00) and improving the staff welfare (= 2.11) to a low extent. Meanwhile, the community was revealed to play their roles in preserving the cordial relationship with schools (= 3.18) to a great extent. This implicates that a proper awareness and orientation of the community members on their roles in the administration of school is pertinent. The study therefore recommends that the Ministry of Education should organized quarterly seminar, workshop, and conferences for the principals, teachers and community members to sensitize them on the need of community members in the administration of secondary schools.